Source of two-dimensional electron gas in unintentionally doped AlGaN/GaN multichannel high-electron-mobility transistor heterostructures - Lingaparthi, R. (2021)
Unintentionally doped (UID) AlGaN/GaN-based multichannel high electron mobility transistor (MC-HEMT) heterostructures have been demonstrated on the SiC substrate using plasma-assisted molecular beam epitaxy. The MC-HEMT heterostructure with a GaN channel thickness of 100 nm resulted in a cumulative two-dimensional electron gas (2DEG) concentration of 4.3 × 1013 cm-2 across six GaN channels. The sample showed sheet resistances of 170 ω/sq. and 101 ω/sq. at room temperature and 90 K, respectively. The source of 2DEG in the buried GaN channels of the heterostructure was investigated. The C-V measurements conducted on UID MC-HEMTs excluded the possibility of the valence band being the source of 2DEG and the consequent formation of two-dimensional hole gas at the buried GaN-channel/AlGaN-barrier interfaces. A comparison of the experimentally obtained 2DEG concentration with the simulated data suggests the presence of donor-like trap states, situated at 0.6 to 0.8 eV above the valence band at the buried GaN-channel/AlGaN-barrier interfaces, which act as the source of 2DEG in UID MC-HEMT heterostructures.